A randomized noninferiority trial evaluating remotely-delivered stepped care for depression using internet cognitive behavioral therapy (CBT) and telephone CBT. (December 2019) - Mohr, David C.; Lattie, Emily G.; Tomasino, Kathryn Noth; Kwasny, Mary J.; Kaiser, Susan M.; Gray, Elizabeth L.; Alam, Nameyeh; Jordan, Neil; Schueller, Stephen M.
Abstract: This trial examined whether a stepped care program for depression, which initiated treatment with internet cognitive behavioral therapy, including telephone and messaging support, and stepped up non-responders to telephone-administered cognitive behavioral therapy (tCBT), was noninferior, less costly to deliver, and as acceptable to patients compared to tCBT alone. Adults with a diagnosis of major depressive episode (MDE) were randomized to receive up to 20 weeks of stepped care or tCBT. Stepped care (n = 134) was noninferior to tCBT (n = 136) with an end-of-treatment effect size of d = 0.03 and a 6-month post-treatment effect size of d = −0.07 [90% CI 0.29 to 0.14]. Therapist time in stepped care was 5.26 (SD = 3.08) hours versus 10.16 (SD 4.01) for tCBT (p < 0.0001), with a delivery cost difference of -364.32 [95% CI -423.68 to -304.96]. There was no significant difference in pre-treatment preferences ( p = 0.10) or treatment dropout (39 in stepped care; 27 in tCBT; p = 0.14). tCBT patients were significantly more satisfied than stepped care patients with the treatment they received (p < 0.0001). These findings indicate that stepped care was less costly to deliver, but no less effective than tCBT. There was no significant difference in treatment preference or completion, however satisfaction with treatment was higher in tCBT than stepped care. Trial registration: clinicaltrials.gov Identifier: NCT01906476. Highlights: Stepped care used internet cognitive behavioral therapy (iCBT) + telephone CBT [tCBT]). Stepped care was noninferior to tCBT for depression at both post-treatment and 6-month follow-up. Stepped care cost approximately half to administer, compared to tCBT. Treatment dropout for stepped care was not significantly different from tCBT.